Corruption as an Entrepreneurship Phenomenon: The Case of the Electronic Identity Card (EKTP) in Indonesia - Solihin, Ismail (International Journal of Psychosocial Rehabilitation, 2020)
Corruption is a destructive entrepreneurial activity because the perpetrators of corruption only become rent seekers. Corruption is born because of the existence of relations between the government, the House of Representatives, and institutional entrepreneurs who together perceive the benefits to be obtained through the implementation of budgeted government activities. This study shows the fulfillment of elements of entrepreneurial activities carried out by perpetrators of corruption, such as: identification of business opportunities; resource collection; establishment of business organizations; production of goods or services; and bearing the risk. Thus, corruption can be seen as entrepreneurial activity.